Analysis of Agricultural Drought and its Effects on Productivity at Different District of Nepal - Bhandari, Govinda; Panthi, Bhanu B. (Journal of Institute of Science and Technology, 2015)
This paper examines the variation of productivity brought by the change in rainfall and temperature and the possible cause and effect of 1992 agricultural drought in Nepal. Agriculture seems to be very sensitive to short term changes in weather and that leads effects to the production of different crops. Productivity of different crops was analyzed in 1992 at regional level and different ecological zones. In 1992, insufficient rainfall (monsoon) might have caused the drought and reduces ground water recharge. This imposed effect to the change in normal rainfall pattern and duration of monsoon season. The year 1992 was seems to be dry, which has decreased the yield of major cereals crops in 3 districts of Western Development Region, 5 districts of Mid Western Development Region and 4 districts of Far Western Development Region. A total of 12 districts were significantly affected by drought in 1992 based on the meteorological data and productivity of crops. Journal of Institute of Science and Technology, 2014, 19(1): 106-110